2005
DOI: 10.1074/jbc.m508476200
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Kinase C/Ras/ERK Signaling Pathway Activates Myeloid Fibronectin Receptors by Altering β1 Integrin Sialylation

Abstract: Here we report that myeloid cells differentiating along the monocyte/macrophage lineage down-regulate the ST6Gal-I sialyltransferase via a protein kinase C/Ras/ERK signaling cascade. In consequence, the ␤1 integrin subunit becomes hyposialylated, which stimulates the ligand binding activity of ␣5␤1 fibronectin receptors. Pharmacologic inhibitors of protein kinase C, Ras, and MEK, but not phosphoinositide 3-kinase, block ST6Gal-I down-regulation, integrin hyposialylation, and fibronectin binding. In contrast, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 31 publications
11
71
1
Order By: Relevance
“…2A, lower panel). It should be noted that the similar mobility on the SDS-PAGE between ⌬1-3 and ⌬7,8 mutants, or between ⌬4-6 and ⌬9-12 mutants, further supported the notion that site 2 and site 11 do not carry N-linked glycans as reported by Seales et al (33). The integrin ␤1 subunit associates with multiple ␣ subunits to form various heterodimers, which may stabilize its expression.…”
Section: Construction Of Various Integrin ␤1 Mutants By the Mutagenessupporting
confidence: 58%
See 1 more Smart Citation
“…2A, lower panel). It should be noted that the similar mobility on the SDS-PAGE between ⌬1-3 and ⌬7,8 mutants, or between ⌬4-6 and ⌬9-12 mutants, further supported the notion that site 2 and site 11 do not carry N-linked glycans as reported by Seales et al (33). The integrin ␤1 subunit associates with multiple ␣ subunits to form various heterodimers, which may stabilize its expression.…”
Section: Construction Of Various Integrin ␤1 Mutants By the Mutagenessupporting
confidence: 58%
“…1. Reportedly, 10 of these sites are normally N-glycosylated, whereas sites 2 and 11 do not normally carry N-linked glycans (33). However, which of the 12 N-glycosylation sites are important for biological function of the subunit remains unknown.…”
Section: Construction Of Various Integrin ␤1 Mutants By the Mutagenesmentioning
confidence: 99%
“…We found that N-glycosylation on the β-propeller domain of the α5 subunit (S3-5) is essential for its heterodimer formation and its biological functions such as cell spreading, cell migration and cytoskeletal formation, as well as for the proper folding of the α5 subunit [30]. Seales et al reported that the I-like domain on the β1 subunit, which could be the partner of the β-propeller of the α5 subunit [31], supporting the importance of N-glycans on the β-propeller. The crystal structure of integrin αVβ3 has been successfully revealed, and the main contact between the αV and β3 subunit is the β-propeller on the αV and A domain on β3 with hydrophobic, ionic, and other interactions [32,33].…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…The humoral response (28 -30), maintenance of myeloid homeostatic balance (22), modulation of dendritic cell activity (31), T cell functionality (32), and integrin signaling (33)(34)(35) are but a few physiologic processes with implicated ST6Gal-1 participation. The idea of ST6Gal-1 pleiotropy Expression of (top left) total ST6Gal-1 mRNA, (top right) P1-transcribedST6Gal-1 mRNA that contains the unique Exon H sequence (2), and (bottom) selected hepatic sialyltransferases were measured by real-time PCR relative to the expression of RPL32, a ribosomal protein, as a reference standard.…”
Section: Discussionmentioning
confidence: 99%